Board characteristics and earnings forecasts accuracy in IPO prospectuses - Tomasz Sosnowski; Anna Wawryszuk-Misztal (International Journal of Management and Economics, 2019)
Using a sample of 104 companies that conducted initial public offering (IPO) on the Warsaw Stock Exchange between 2006 and 2016, we investigated the relationship between the accuracy and bias of the earnings forecast disclosed in the IPO prospectus and the firm corporate governance attributes. Applying multiple Ordinary Least Squares (OLS) regressions models, we focused on the role of the board size, the percentage of women on the board, the board age diversity measure, and the proportion of shares owned by the members of the board. Generally, our findings show that some characteristics of management and supervisory board improve the usefulness of earnings forecasts' credibility. Especially, a more diversified board in terms of age and higher management ownership results in more accurate forecasts. This is the first study giving an insight into the role of supervisory and management board characteristics on precision of earnings forecasts revealed in the prospectus by Polish IPO companies.
Keywords: G34; G32; G23; 650; initial public offering; earnings forecast; management and supervisory board